Managing Systems Approach to Earthquake Disaster Preparedness Problems - Tuladhar, Bhagawan Ratna (Administration and Management Review, 2009)
It is imperative to focus attention on Earthquake Disaster preparedness and pre-disaster planning to reduce material losses and minimize human sufferings. A consistent and coherent policy is needed towards management of earthquake disasters due to the fact that Nepal is an earthquake prone country. With modernization growing population and migration, a metropolis like Kathmandu is facing challenges such as unplanned settlements and deplation of soil and water. A terrible gap in institutional capacity to manage new challenges is visible everywhere. The author in this article looks at this aspect seriously and tacitly contends that the strengthening of institutional capabilities for environmental preparedness for disaster management is the number one priority for Metropolitan Kathmandu. Administration and Management Review Vol. 21 No. 1, January 2009, Page 32-45